2010
DOI: 10.3390/md8051650
|View full text |Cite
|
Sign up to set email alerts
|

On the Chemistry, Toxicology and Genetics of the Cyanobacterial Toxins, Microcystin, Nodularin, Saxitoxin and Cylindrospermopsin

Abstract: The cyanobacteria or “blue-green algae”, as they are commonly termed, comprise a diverse group of oxygenic photosynthetic bacteria that inhabit a wide range of aquatic and terrestrial environments, and display incredible morphological diversity. Many aquatic, bloom-forming species of cyanobacteria are capable of producing biologically active secondary metabolites, which are highly toxic to humans and other animals. From a toxicological viewpoint, the cyanotoxins span four major classes: the neurotoxins, hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
302
0
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(346 citation statements)
references
References 167 publications
(182 reference statements)
4
302
0
17
Order By: Relevance
“…In Europe, toxic N. spumigena blooms have frequently been reported in the Baltic Sea and because of that NOD is considered to be one of the most abundant naturally occurring compounds in this brackish-water environment (Pearson et al, 2010). Production of NOD in situ and in laboratory conditions has been well studied.…”
Section: Nodularin -Production and Limiting Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Europe, toxic N. spumigena blooms have frequently been reported in the Baltic Sea and because of that NOD is considered to be one of the most abundant naturally occurring compounds in this brackish-water environment (Pearson et al, 2010). Production of NOD in situ and in laboratory conditions has been well studied.…”
Section: Nodularin -Production and Limiting Factorsmentioning
confidence: 99%
“…Comprehensive reviews of cyanotoxins in aquatic systems have been published in the last few years (e.g. Van Apeldoorn et al, 2007;Pearson et al, 2010) and so the present review will focus on the one toxin most commonly found and primarily studied in brackish-water and estuarine environments, NOD.…”
Section: Further Cyanotoxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cyclic hepatotoxic peptides microcystins (MCs) are among the most important and by far themost studied cyanotoxins. This group of toxins can be produced by by a number of cyanobacteria genera such as Microcystis, hjycdq@hhu.edu.cn, hjycyq@hhu.edu.cn) Anabaena, Plankothrix and Nostoc had been proved to be acute hepatotoxicity [17], [18]. Though MCs mainly inhibit the serine/threonine phosphatases (PP1 and PP2A), they may also promote tumor formation, induce apoptosis, and present long-term chronic toxic effects on wildlife, domestic animals and humans [19]- [22].…”
Section: Introductionmentioning
confidence: 99%